Importance of using flashcards to learn basic english vocabulary in kindergarten - Sinchi Sibri, Jessica Paola; Sinchi Sinchi, Tania Esmeralda
The purpose of this project is to determine that teaching materials such as flashcards are an important resource in teaching English to young learners. Flashcards are resources that positively influence children´s motivation to learn English and facilitate the teaching-learning process. Educational Materials allow teachers to improve their methodology. Teachers have to be facilitators, guides and models to their students. For this reason, they should use different kinds of resources to achieve successful classes. One of these resources is flashcards which are very useful material to teach Basic English vocabulary. This means that the words children are learning will be easily understood and in the same way easily used to communicate. Teaching vocabulary improves students? speaking, listening, reading, and writing skills. This project describes how teachers can use flashcards as part of their methodology to teach children vocabulary.